Sosialisasi Hasil Penelitian tentang Efektifitas Pupuk Organik, Anorganik dan Ampas Biogas Terhadap Pertumbuhan Tanaman Kangkung pada Dusun Cibitung, Desa Ponggang - Trifenaus Prabu Hidayat; Andre Sugioko; Enny Widawati; David Antonius (Jurnal Pengabdian Masyarakat Charitas, 2025)
Cibitung Hamlet, Ponggang Village is one of four partner villages of the Industrial Engineering Study Program of Atma Jaya University (UAJ) in community service activities. Continuing economic development for Ponggang Village, the community service team saw an opportunity in Cibitung Hamlet to plant water spinach as a selling product and increase vegetable consumption for the Ponggang Village community. To support the planting of water spinach, fertile soil, sunlight, and water are needed. Fertilization is really necessary to increase or maintain plant fertility by adding artificial or natural nutrients. The Community Service Team conducted a preliminary study on the effect of organic fertilizers, inorganic fertilizers, fertilizers from biogas dregs (bioslurry), and no fertilizers, using the soil in Cibitung Hamlet on the growth of water spinach. Based on the results of the study, fertilizers using biogas dregs provided heavy metal content values below the limit and also provided a fairly good level of water spinach growth compared to the treatment of organic fertilizers, inorganic fertilizers, and no fertilizers. The results of his study were socialised to the community of Cibitung Hamlet, Ponggang Village in the form of community service